The Utilization of Feather Meal Fermented Using Bacillus sp. from Giant Freshwater Prawn in diet forSilver Pompano (Trachinotus blochii, Lac) Fingerling - Aisenodni, Aga Fifty; Adelina, Adelina; Suharman, Indra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe research was conducted on May to July 2017. The purpose of this research was to know the best percentage of fermented feather meal in diet and effect on growth of silver pompano (Trachinotus blochii, Lac) fingerling. This study uses a completely randomized design (CRD) with one factor,five treatment and three replications. The research used fish with initial average weight of 0,9 g. Fish were reared in net cage of 1x1x1 m3with the stocking density of 20 fish/net cage. Treatments with fermented feather meal, P0 (0%), P1 (5%), P2 (10%), P3 (15%), P4 (20%). Feed protein content range between 43,94-46,33%. The result show that fermented feather meal give significant effect (P<0,05) on growth, feed efficiency and protein retentions.This result of this study suggest that fermented feather meal can be used as feed material of silver pompano up to 15% from total amount of feed.Keyword: Bacillus sp., feather meal, fermented,fish feed, silver pompano (Trachinotus blochii, Lac)